Perceived Barriers and Needs of Dietary Macro Nutrient Intake in Adolescent Schoolgirls in Small Island - Healthy Hidayanty; Abdul Razak Thaha; Syamsuar Manyullei; Rahayu Indriasari; Mesra Rahayu; Devintha Virani; Leng Huat Foo (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Adolescence is an important period of rapid change in biological, psychosocial and cognitive growth and development marked by significant increases in nutrition and energy needs. The study aimed to explore perceived barriers and needs regarding dietary macronutrient intake in adolescent girls in Barrang Lompo Island in Makassar City, South Sulawesi Province, Indonesia. The qualitative design drew on constructs from social cognitive theory. The sample consisted of 18 adolescent girls and their mothers from grades 8 to 11 whose dietary macronutrient intake was less than the recommended dietary allowance. A semi-structured interview protocol was used to explore perceived barriers and needs regarding dietary macronutrient intake, and the data were subjected to thematic analysis and analytic generalization. To ensure adequate dietary intake, adolescent girls need support from family and friends and access to preferred foods. Barriers include laziness about eating key foods, feelings of fullness due to snacking, addiction to cellphones, and lack of raw foodstuffs for making their favorite dishes. Social cognitive theory used to identify needs and barriers showed environmental and individual factors from adolescents play important role in appropriate food consumption in teenage girls. The findings may help to improve future interventions to enhance dietary patterns in adolescent girls who live in small island.